The impact of obesity in rehabilitation: a mismatch between staff perception and hospital outcomes. Issue 3 (30th January 2022) - Oakley, Lisa; Soh, Sze-Ee; Kimmel, Lara; Mulvey, Nina; Curtis, Heather; Holland, Anne E.
Abstract: Purpose: To establish the prevalence of obesity in an inpatient rehabilitation setting, examine its impact on hospital outcomes, and explore staff perceptions of caring for patients with obesity. Methods: A retrospective audit of inpatients admitted to a sub-acute rehabilitation hospital over 12 months. Hospital outcomes included length of stay (LOS), Functional Independence measure (FIM), and discharge destination. Linear regression models were used to determine whether obesity was associated with hospital outcomes. Staff working on rehabilitation wards were invited to complete a survey exploring their perceptions on caring for those who are obese. Results: Of 1280 episodes of care, 359 (28%) patients were classified as obese with a body mass index ≥30 kg/m 2 . Obesity was not associated with LOS or functional improvement after controlling for age, gender, and admission FIM. One hundred and twelve hospital staff (response rate 71%) completed the survey. Most rated their bariatric care knowledge as average (45%) or good (36%). The majority (60%) perceived that patients with obesity have longer LOS than those who are non-obese. Conclusion: One-third of patients admitted to inpatient subacute rehabilitation were classified as obese. Whilst obesity was not associated with poorer hospital outcomes, staff perceived that obesity negatively impacts on care requirements and LOS. Implications for rehabilitation: A third of patients admitted to a public, inpatient rehabilitation setting may be classified as obese based on their body mass index. Although staff perceived that obesity negatively impacts on length of stay and functional gains, there was no evidence that obesity was associated with poorer hospital outcomes. Patients who are classified as obese were able to achieve comparable hospital outcomes including length of stay in the rehabilitation setting to those who are not obese.